Selection method of the project management methodology and its application - Kononenko, Igor; Kharazii, Anna; Iranik, N. (IEEE Ukraine Section I&M / CI Joint Societies Chapter, 2013)
The task of selecting the methodology for managing a specific project is analyzed. The method, consisting of 2 stages, is suggested. At the first stage a project manager has to fill out a questionnaire. Based on the obtained results, a corresponding project management methodology is suggested. The second stage is devoted to evaluation of the work content of managing the project with the methodologies under study, the cost and risks of their application. Solution for the three-criterial optimization problem of selecting a methodology is suggested. An example of application of the method for selecting the methodology is provided for managing an IT project.
Keywords: project management; methodology; questionnaire; three-criterial optimization